2016
DOI: 10.1126/science.aaf2022
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “Sensitivity of seafloor bathymetry to climate-driven fluctuations in mid-ocean ridge magma supply”

Abstract: Tolstoy reports the existence of a characteristic 100 thousand year (ky) period in the bathymetry of fast-spreading seafloor but does not argue that sea level change is a first-order control on seafloor morphology worldwide. Upon evaluating the overlap between tectonic and Milankovitch periodicities across spreading rates, we reemphasize that fast-spreading ridges are the best potential recorders of a sea level signature in seafloor bathymetry. We acknowledge the clear distinction made by Tolstoy (1) between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…There are no significant peaks in the bathymetry power spectrum at any of the Milanković‐cycle periods (100, 41, and 23 kyr) as reported by Crowley et al (), supporting the idea that ocean floor bathymetry formed at slow‐spreading MORs is not sensitive to fluctuations in melt supply triggered by sea level change (Goff, ; Goff et al, ; Olive et al, , ).…”
Section: Time‐series Analysissupporting
confidence: 71%
“…There are no significant peaks in the bathymetry power spectrum at any of the Milanković‐cycle periods (100, 41, and 23 kyr) as reported by Crowley et al (), supporting the idea that ocean floor bathymetry formed at slow‐spreading MORs is not sensitive to fluctuations in melt supply triggered by sea level change (Goff, ; Goff et al, ; Olive et al, , ).…”
Section: Time‐series Analysissupporting
confidence: 71%
“…This hypothesis is consistent with previous studies (Bohnenstiehl & Carbotte, ; Malinverno & Cowie, ) that successfully model fault scaling parameters (spacing, length, and throw) as random distributions governed by scaling laws. The work of Olive et al () also provides supporting evidence; after stacking conjugate corridor profile of the data used in the Crowley et al () study, they found that that the spectral peaks that had been attributed to Milankovitch cycles disappeared. Hence, even with just two independent profiles, it is clear that the main abyssal hill peaks and valleys do not stack coherently as a function of age.…”
Section: Seafloor Stacking Methodologymentioning
confidence: 84%
“…The Milankovitch cycle hypothesis has garnered significant attention (Conrad, 2015;Hand, 2015), in large part because the potential implications are far-reaching, that is, that abyssal hills, the most common landform on Earth (Menard, 1967), could provide a record of global sea level fluctuations and climate history over many tens of millions of years. However, the hypothesis has been the focus of substantial criticism (Goff, 2015;Macdonald, 2015;Olive et al, 2015) and resulted in vigorous discussion (Crowley et al, 2015b;Huybers et al, 2016;Olive et al, 2016aOlive et al, , 2016bTolstoy, 2016). There are four important criticisms of the Milankovitch cycle hypothesis and the basis for its assertion: (1) Abyssal hills are dominantly fault-bounded structures that form kilometers off axis, rather than volcanic constructs, as evidenced by decades of observational studies (Macdonald, 2015;Macdonald et al, 1996); therefore, the primary "signal" of abyssal hill topography is a record of MOR faulting rather than magmatic output; (2) lava emplacement on fast-spreading MORs tends to occur as sheet flows often extending several kilometers from the zero-age axis (e.g., Escartín et al, 2007;Macdonald et al, 1989;Mitchell, 1995;Soule et al, 2005), which complicates the relationship between crustal age and distance from the axis over temporal scales appropriate for the Milankovitch cycle hypothesis (Goldstein et al, 1994;Macdonald, 2015); (3) globally, there is an overall decrease in abyssal hill widths with spreading rate (Goff et al, 1997), which is consistent with a faulted origin but contrary to the Milankovitch cycle hypothesis prediction of an increase with spreading rate (Goff, 2015;Olive et al, 2015); and (4) the observational evidence of the Crowley et al (2015a) study in particular relied on a single profile and thus should be considered as anecdotal evidence for a hypothesis that makes predictions on regional or even global scales.…”
Section: Introductionmentioning
confidence: 99%